A case report of sudden-onset auditory neuropathy spectrum disorder associated with Brown-Vialetto-Van Laere syndrome (riboflavin transporter deficiency). (3rd March 2022) - Gedik Soyuyuce, Ozlem; Ayanoglu Aksoy, Elif; Yapici, Zuhal
Abstract: Objective: The purpose of this paper is to describe a child with auditory neuropathy spectrum disorder (ANSD) associated with Brown-Vialetto-Van Laere (BVVL) syndrome, which is a rare, inherited, neurodegenerative disorder that is caused by defects in riboflavin transporter genes. Design: We report the audiological and clinical profile of a child who presented with a complaint of sudden loss of speech understanding associated with an atypical form of ANSD. He was later diagnosed with BVVL. Study Sample: An 11-year-old boy with ANSD associated with BVVL. Results: The patient's severe neurological symptoms improved within a year of supplementation with high doses of riboflavin. His fluctuating hearing loss and 0% WDS remained unchanged. The patient was able to use hearing aids without any discomfort after treatment initiation, but he stopped using them again due to a lack of benefit in speech understanding. Although cochlear implantation was recommended, the patient and his family decided not to consider it for another year since they still had hope for complete recovery. Conclusions: Sudden-onset ANSD can be the earliest sign of undetected BVVL syndrome. Early detection of BVVL is crucial since all symptoms can be reversible with an early intervention of high doses of riboflavin supplementation.